posted by Olivea on .
I'm not really sure on how to prove statements are right with properties as reasons. How would you solve this?
If x + c = 0, then x = -c
2. (x+c)+(-c) = 0 + (-c)
3. x + [c+(-c)] = 0 + (-c)
4. x + 0 = 0 + (-c)
5. x = (-c)
Would 5 be the substitution property?
Does that mean 1 would be be reasoned by the substitution property?
yes i think that's correct coz when we do this sum ,,,we do it in this way
-c -c (subtracting x both side)
that is x=-c
Oh, thank you. For number 2, I originally had the definition of addition, but I was marked wrong. I'm not very sure, but wouldn't it be considered the definition of addition if you were adding (-c) to both sides? And also, in this case x+c would equal 0 so that would be the reason you are substituting 0 for x+c in number 2 as well. I don't really understand properties..
yes that's it/......u got it